Preparation of N2, N2,7-trimethylguanosine affinity columns - Espuny, Ruth; Bahia, Diana; Cicarelli, Regina Maria Barretto [UNESP]; Codony, Carles; Khaouja, Amina; Aviñó, Anna Maria; Eritja, Ramon; Bach-Elias, Montse (Taylor & Francis, 1999)
2,2,7-trimethylguanosine (TMG) binding proteins from human cells were purified through TMG-affinity columns. TMG synthesis was improved and the TMG obtained was shown to be similar to the TMG in the 5' cap of the UsnRNAs. The eluates obtained with TMG-affinity chromatographies were very different from those isolated with m7G-affinity columns, thus suggesting that specific TMG- binding proteins were obtained. The fraction may be enriched with factors associated with import and/or hypermethylation of UsnRNPs.
Keywords: binding protein; guanosine derivative; small nuclear RNA; antibody; carrier protein; drug derivative; fungal protein; guanosine; hemocyanin; keyhole limpet hemocyanin; keyhole-limpet hemocyanin; monoclonal antibody; N(2),N(2),7 trimethylguanosine; N(2),N(2),7-trimethylguanosine; nuclear protein; sepharose; serum albumin; affinity chromatography; animal experiment; extraction; human; mouse; nonhuman; nucleotide metabolism; protein methylation; protein purification; spliceosome; synthesis; animal; cell nucleus; chemistry; cytoplasm; HeLa cell; instrumentation; isolation and purification; methodology; rabbit; Saccharomyces cerevisiae; Animals; Antibodies; Antibodies, Monoclonal; Carrier Proteins; Cell Nucleus; Chromatography, Affinity; Cytoplasm; Fungal Proteins; Guanosine; Hela Cells; Hemocyanin; Humans; Mice; Nuclear Proteins; Rabbits; Sepharose; Serum Albumin